Empire and the megamachine: comparing two controversies over social media content - Stephanie Hill (Internet Policy Review, 2019)
This paper presents the results of a thematic analysis of hearings held before the US senate in 2017 with representatives of social media companies and close coverage from industry groups of advertising boycotts of social media. In response to the public pressure, social media companies increased their investment in machine learning and human moderation to remove inappropriate content and increased transparency initiatives. The two scenarios indicate the importance of content to questions of platform governance and the ability of the advertising industry to act as a platform regulator. This paper uses the political economic analysis of Harold Innis and theoretical work on the megamachine as a framework for understanding how governance may be enacted through commercial systems before and around government policy tools. It argues that social media companies’ actions indicate an expanded role for marketing and advertising as governors of media content delivery, resulting in the efficient administration of advertiser concerns while democratic representatives take a comparatively slow road.